New Tuning Conditions for Semiglobal Exponential Stability of the Classical PID Regulator for Rigid Robots. (15th October 2015) - Orrante-Sakanassi, Jorge; Hernandez Guzman, Victor M.; Santibanez, Victor
In this paper, we introduce a novel tuning procedure to ensure semi-global exponential stability for the classical PID control of rigid robots. This tuning procedure is expressed in terms of conditions which are more relaxed than those proposed previously in the literature. This allows us to perform, for the first time, experimental tests with a classical PID controller ensuring semi-global exponential stability. Finally, we show numerically that previous formal tuning procedures in the literature result in very large controller gains which prohibit the performance of any experimental test.